The application of teledentistry for Saudi patients' care: A national survey study - Soulafa A. Almazrooa; Ghada A. Mansour; Sana A. Alhamed; Sarah A. Ali; Sara K. Akeel; Nada A. Alhindi; Osama M. Felemban; Hani H. Mawardi; Nada O. Binmadi (Elsevier, 2021)
Background/purpose: Teledentistry has emerged as a new communication tool in various dental disciplines around the world. The aim of this study was to investigate the applicability and reliability of teledentistry in the field of diagnostic dentistry and explore the perception of Saudi dentists of its benefits and concerns. Materials and methods: An electronic survey with 40 questions was developed, validated and distributed electronically by email and social media channels to dentists from different specialty in Saudi Arabia. Collected data were analyzed for statistical significance. Results: A total of 148 dentists completed the survey. The current data demonstrated that 50% of study participants have had applied teledentistry in their clinical practice. Out of all, 90% have computers in their dental offices and 72% have been using electronic medical records in which radiographs and clinical images are uploaded. Most participants had smart phones (91%), in which they were used more commonly (74.3%) than conventional cameras (54.1%) to capture and share patients' clinical images over communication applications (74.3%) and less likely through emails (62.2%). Overall, 83% were confident that teledentistry can improve daily dental practice, specifically in the fields of oral radiology followed by endodontics and oral medicine. Conclusion: Teledentistry is an emerging tool with potential to improve the delivery of diagnostic dental care for communities with limited or no access to dental specialists. As of today, teledentistry has not been truly implemented by the Saudi dental community. Development of national programs to educate the public and promote teledentistry among dental practitioners are warranted.